Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantu Alat Praktikum Sederhana Terhadap Hasil Belajar Siswa SMA Negeri 1 Sausu - Risky Restu Nahrowi; Ratman Ratman (Universitas Tadulako, 2021)
This research was conducted to determine the effect of learning sail on class Xa students as an experimental class using the guided inquiry method assisted by simple practical tools and class Xg using conventional methods on electrolyte solution material. This type of research is experimental research using pretest-posttest control. The population is students of class Xa and Xg SMA Negeri 1 Sausu. The technique used in sampling is purposive sampling, which is a non-random sampling technique in which the researcher determines the sample by determining special characteristics that are in accordance with the research objectives. The sample in this study was 28 in the experimental class and 27 in the control class. Testing the research data using statistical analysis of one-party t-test with prerequisite test with normality test and homogeneity test. The results of the analysis of the data obtained on the normality and homogeneity tests are prerequisite tests for the t-test statistics. Based on the normality test of the learning outcomes test data for the experimental class, the value of 2count < 2 (5.91623 < 5.99) and the normality of the data for the control class obtained 2count < 2table (5.7952 < 7.81). These results show that both the experimental class and the control class have data that are normally distributed. This means that the data obtained has an even distribution between low, medium, and high student learning outcomes, which meet the normal curve. be accepted. So it can be concluded that there is no difference in variance between the control class and the experimental class, so the data is homogeneous. So this research concludes that guided inquiry learning has an effect on student learning outcomes.